Icariin Attenuates High Glucose-Induced Apoptosis, Oxidative Stress, and Inflammation in Human Umbilical Venous Endothelial Cells - Sun, Si; Liu, Le; Tian, Xiaojun; Guo, Yanghongyun; Cao, Yingkang; Mei, Yunqing; Wang, Changhua (Planta Medica, 2019)
Endothelial dysfunction is closely associated with diabetic complications. Icariin, a flavonoid glycoside isolated from the Epimedium plant species, exhibits antidiabetic properties. However, its impact on endothelial function remains poorly understood, particularly under hyperglycemia. In this study, we investigated the potential protective effect of icariin on high glucose-induced detrimental effects on vascular endothelial cells. Human umbilical venous endothelial cells were incubated in media containing 5.5 mM glucose (normal glucose) or 25 mM glucose (high glucose) in the presence or absence of 50 µM icariin for 72 h. We found that high glucose markedly induced cell apoptosis, enhanced reactive oxygen species generation, and elevated expression levels of inflammatory factors and cell adhesion molecules, which were greatly subdued by icariin supplementation. In conclusion, icariin exerted a beneficial effect on high glucose-induced endothelial dysfunction. This new finding provides a promising strategy for future treatment of diabetic vascular complications.
Keywords: icariin; antidiabetic; inflammation; apoptosis; Epimedium sp.; Berberidaceae; endothelial cell